Masjid-masjid di Dunia Melayu Nusantara - Tawalinuddin Haris (Lajnah Pentashihan Mushaf Al-Qur'an, 2010)
Mosque is functioned not only as a place to prostrate, but more than that is the place where muslims can do some other activities such as education, preaching and activities relating to Islamic culture. The development of the building of the mosque inÂ the Malay World of Indonesian ArchipelagoÂ (Nusantara) is closely connected to the custom and local culture, either from the shape of the building, architecture, elements or the shape of the architectures. This writing is discussing about the early development of the mosques in the Malay world of IndonesianÂ archipelago (Nusantara) and their special characteristics from each region which is much influenced by its the local culture.